A new 2-D multi-stable chaotic attractor and its MultiSim electronic circuit design - Sundarapandian Vaidyanathan; Aceng Sambas; Mohamad Afendee Mohamed; Mustafa Mamat; W. S. Mada Sanjaya; Sudarno Sudarno (Institute of Advanced Engineering and Science, 2021)
A new multi-stable system with a double-scroll chaotic attractor is developed in this paper. Signal plots are simulated using MATLAB and multi-stability is established by showing two different coexisting double-scroll chaotic attractors for different states and same set of parameters. Using integral sliding control, synchronized chaotic attractors are achieved between drive-response chaotic attractors. A MultiSim circuit is designed for the new chaotic attractor, which is useful for practical engineering realizations.